The influence of ventilation mode and personnel walking behavior on distribution characteristics of indoor particles. (February 2019) - Lv, Yang; Wang, Haifeng; Zhou, Yuwei; Yoshino, Hiroshi; Yonekura, Hiroshi; Takaki, Rie; Kurihara, Genta
Abstract: People spend nearly 90% of their time daily in various indoors, hence indoor environment is important for mortal survival and activity, which affected human health directly. Indoor particulate pollution has become an issue of increasing concern for human beings. Personnel walking behavior and ventilation mode will significantly affect the transfer characteristics of indoor particles. This paper analyzes the effect of walking process on indoor particle resuspension, and different ventilation modes (ceiling exhaust and slit exhaust) on the removal of indoor particulate concentration in experimental and theoretical models. The results show that the particle diffusion model under walking is in good agreement with the experimental results. The particles with different sizes have different diffusion characteristics during walking due to the surface deposition and resuspension rate. Particles of 1.0–3.0 μm have the fastest velocity and the largest amount in suspension, while the smallest for 0.5–1.0 μm particles. Different ventilation modes have different effects on the removal of indoor particles. The particles attenuation index is higher under slit exhaust mode, therefore the ventilation effect is higher than ceiling ventilation mode. Highlights: The effect of human walking process on indoor particle resuspension and removal was analysed. Different size particles have different diffusion characteristics during the walking process. Different ventilation methods have different effects on the indoor particulate matter removal.